Assisted Reproductive Technologies in Latin America and Europe: a Comparative Analysis of Reported Databases for 2013 - Duarte-Filho, Oscar Barbosa; Bianchi, Paulo Homem de Mello; Lobel, Alexandre Likier Steinberg; Peregrino, Pedro Felipe Magalhães; Piccinato, Carla de Azevedo; Podgaec, Sérgio (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To compare the Latin American and European assisted reproductive technology (ART) registries regarding data accessibility and quality, treatment utilization, effectiveness, safety, and quality of services.Methods We performed an ecological study using data from scientific publications of Latin American and European registries that report cycles initiated during 2013 (the most recent registries available until December of 2017). The summarized data are presented as frequencies, percentages, minimum-maximum values, and absolute numbers.Results Reporting clinics and cycle treatments were unevenly distributed between the participating countries for both registries, although access to ART is 15 times greater in Europe. In Latin America, individual services participate voluntarily reporting started cycles until cancellation, birth or miscarriage, while in Europe it varied among countries. It makes the data available from Latin America more uniform, although lesser representative when compared with European ones, given that reporting is compulsory for most countries. The cumulative live birth rate was better in Latin America. Female age, use of intracytoplasmic sperm injection (ICSI), cycles with transfer of ≥ 3 embryos, as well as multiple pregnancy rates were greater in the Latin American Register of Assisted Reproduction (RLA, in the Portuguese acronym). Assisted reproductive technology complications, such as ovarian hyperstimulation syndrome, hemorrhage, and infections were also higher in Latin America, although they are extremely uncommon in both regions.Conclusion Both regions have points to improve in the quality of their reports. Latin America has produced a more uniform reporting, their clinical results are generally comparable and sometimes higher than the European ones. In contrast, the safety of the treatment was higher in Europe, with lower rates of complications, especially multiple pregnancies.
Keywords: registries; assisted reproductive technique; in vitro fertilization; intracytoplasmic sperm injection; artificial insemination